Research and Development of Seduboo as A Sex Education Media for Teenager - Nanda, Veronika Dexsa; Setyaningsih, Wahyu; Jupriyono, Jupriyono (Poltekkes Kemenkes Jakarta III, 2022)
The era of globalization causes people, especially teenagers, to quickly get information through the internet. It impacts the mindset and lifestyle of teenagers who tend not to filter information correctly and adequately. Misperceptions about sex issues encourage teens to try sex issues without realizing the dangers. This study aims to develop a Sex Education Book (SEDUBOO) as a medium for adolescent sex education. This study uses ten youth cadre respondents to use a Research and Development (R&D) design. The instruments used are expert questionnaires, user response questionnaires, and pre-test and post-test post-test to measure adolescent knowledge related to knowledge of sex education. The results of the study stated that the developed media could be categorized as very feasible, based on the results of the assessment of material experts (90.7%), media experts (94%), and respondents' assessments (94.2%). Adolescent knowledge increased with the pre-test results of 2 respondents in the excellent category and the post-test results of 10 respondents in the excellent category. Media is an essential factor in providing health education. Appropriate media help convey information about sex that can be received appropriately to prevent deviant behaviour.